The Influence of Water Content on the Composting Process of Straw Mixed With Cow Dung - Putra, I Made Pila Antara; Sumiyati; Setiyo, Yohanes (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
This study aimed to determine the effect of water content on the composting process of rice straw and cow dung and to identify the optimal water content for faster composting. Five treatments were applied: P1 (40% water), P2 (45% water), P3 (50% water), P4 (55% water), and P5 (60% water), with 35 kg of material per treatment and a rice straw to cow dung ratio of 3:4. Observed parameters included temperature, water content, yield, pH, nitrogen, carbon, and C/N ratio. The highest peak temperature occurred in the 60% water treatment at 49.8°C, while the lowest peak was in the 40% treatment at 48.4°C. Initial pH ranged from 6.4–6.6 and increased to 6.9–7.2 at the end of composting. The C/N ratio for all treatments met SNI standards, ranging from 18.60–19.01. The resulting compost quality from all treatments complied with SNI 19-7030-2004 standards.